2023
DOI: 10.3389/fspas.2023.1195805
|View full text |Cite
|
Sign up to set email alerts
|

Global insight into a complex-structured heliosphere based on the local multi-point analysis

Abstract: From 29 January to 7 February 2022, the heliosphere was structured with large-scale interacting substructures that appeared with significant dissimilarities at distant observations separated longitudinally by ∼34°. Probing the complexity of the structured heliosphere with multi-point in situ and imaging observations by using a fleet of spacecraft has revealed many unknown facts on the dynamics of large-scale structures in the heliosphere. In this paper, we investigate a complex-structured heliosphere by analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 111 publications
2
5
0
Order By: Relevance
“…We note that Regnault et al (2024) reached the same conclusion for an event observed at SolO and Earth (separated at the time by 0.13 au in heliocentric distance and ∼2°in angular distance), highlighting how small spatial separations can have a prominent impact on the observed CME properties. Likewise, the different flux rope orientations recovered via fitting models (keeping in mind, however, the large uncertainties involved, especially at Bepi, due to the extra data processing described in Appendix B) suggest, in agreement with previous work (e.g., Farrugia et al 2011;Möstl et al 2012;Pal et al 2023), that the axial field direction is more of a "local" quantity rather than part of a coherent, large-scale flux tube. In the case analyzed here, it is possible that interaction with a following HPS had some influence on the orientation of the ejecta at Parker as, e.g., the events investigated by Farrugia et al (2011) andPal et al (2023) involved interactions with stream interaction regions or those studied by Möstl et al (2012) involved CME-CME interactions.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We note that Regnault et al (2024) reached the same conclusion for an event observed at SolO and Earth (separated at the time by 0.13 au in heliocentric distance and ∼2°in angular distance), highlighting how small spatial separations can have a prominent impact on the observed CME properties. Likewise, the different flux rope orientations recovered via fitting models (keeping in mind, however, the large uncertainties involved, especially at Bepi, due to the extra data processing described in Appendix B) suggest, in agreement with previous work (e.g., Farrugia et al 2011;Möstl et al 2012;Pal et al 2023), that the axial field direction is more of a "local" quantity rather than part of a coherent, large-scale flux tube. In the case analyzed here, it is possible that interaction with a following HPS had some influence on the orientation of the ejecta at Parker as, e.g., the events investigated by Farrugia et al (2011) andPal et al (2023) involved interactions with stream interaction regions or those studied by Möstl et al (2012) involved CME-CME interactions.…”
Section: Discussionsupporting
confidence: 88%
“…Likewise, the different flux rope orientations recovered via fitting models (keeping in mind, however, the large uncertainties involved, especially at Bepi, due to the extra data processing described in Appendix B) suggest, in agreement with previous work (e.g., Farrugia et al 2011;Möstl et al 2012;Pal et al 2023), that the axial field direction is more of a "local" quantity rather than part of a coherent, large-scale flux tube. In the case analyzed here, it is possible that interaction with a following HPS had some influence on the orientation of the ejecta at Parker as, e.g., the events investigated by Farrugia et al (2011) andPal et al (2023) involved interactions with stream interaction regions or those studied by Möstl et al (2012) involved CME-CME interactions. Finally, it is interesting to speculate on the uniqueness of the 2022 February 15 event that is the focus of this work.…”
Section: Discussionsupporting
confidence: 88%
“…This event had a higher speed (458 km/s) than CME2, hence, it is likely that the two CMEs interacted during their interplanetary propagation. A recent study by Pal et al (2023) analyzed the dynamics and interactions of CME1, CME2, and CME3 in the interplanetary medium in detail. They approximated the heliocentric distance where CME2 and CME3 possibly merged to be around ∼0.4 au.…”
Section: Solar Sources Of the Moderate Geomagnetic Storms That Impact...mentioning
confidence: 99%
“…Multiple studies have analyzed the solar eruptive events (e.g., Dang et al, 2022;Fang et al, 2022;Gopalswamy et al, 2023;Kataoka et al, 2022;Pal et al, 2023), Joule-heating-mediated changes in thermospheric conditions as a result of their interaction with Earth's magnetosphere (e.g., He et al, 2023;Laskar et al, 2023;Lin et al, 2022;Lockwood et al, 2023), thermospheric drag and orbital decay of the Starlink satellites (e.g., Berger et al, 2023;Guarnieri et al, 2023;Y. Zhang et al, 2022), as well as magnetospheric and ionospheric effects (e.g., Duann et al, 2023;Gulyaeva et al, 2023;Tsurutani et al, 2022;Tsyganenko et al, 2022) due to the geomagnetic storms of 3-4 February 2022.…”
Section: Introductionmentioning
confidence: 99%
“…For example, placing a spacecraft within Mercury's orbit would give several days lead time, but the solar wind structures seen by the spacecraft may have evolved significantly after traveling to Earth (Palmerio et al, 2022;Rodríguez-García et al, 2022). While several case studies have already shown how an upstream spacecraft can be useful in predicting the arrival time and geo-effectiveness (Amerstorfer et al, 2018;Kubicka et al, 2016;Lindsay et al, 1999;Pal et al, 2023;Rollett et al, 2014), such a concept has never been attempted in real time.…”
Section: Introductionmentioning
confidence: 99%